Purchase for Profit: Public-private partnerships and Canada’s health care system - Leach, Nicole (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2017)
Book Review of Purchase for Profit: Public-private partnerships and Canada’s health care system (2015) by Heather Whiteside, Toronto: University of Toronto Press.